2021
DOI: 10.1039/d1py01165k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient vinylic addition polymerization of 5-vinyl-2-norbornene using benzylic palladium complexes as precatalysts

Abstract: In contrast with the parent norbornene, the vinylic addition polymerization of substituted norbornene derivatives is difficult to achieve. We have found that benzylic palladium complexes are suitable precatalysts in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Mechanistic studies of such catalysts revealed that an end group of the polymer chain contains the functional groups from the catalysts used. [53,78] For example, Wu et al confirmed the incorporation of Me group from the PdÀ Me moiety of Pd69b into growing polymer chains using in-situ NMR monitoring of norbornene oligomerization (Figure 22a). [80] The catalyst was not eliminated or decomposed, and the slow initiation of polymerization was attributed to the competitive coordination between NB and acetonitrile.…”
Section: Initiation Of Vapmentioning
confidence: 97%
See 3 more Smart Citations
“…Mechanistic studies of such catalysts revealed that an end group of the polymer chain contains the functional groups from the catalysts used. [53,78] For example, Wu et al confirmed the incorporation of Me group from the PdÀ Me moiety of Pd69b into growing polymer chains using in-situ NMR monitoring of norbornene oligomerization (Figure 22a). [80] The catalyst was not eliminated or decomposed, and the slow initiation of polymerization was attributed to the competitive coordination between NB and acetonitrile.…”
Section: Initiation Of Vapmentioning
confidence: 97%
“…developed cationic Pd complexes with η 3 ‐benzyl‐ligand ( Pd63−Pd68 , Figure 17). [14a,78] This ligand can be readily converted to σ‐benzyl‐ligand to recover the benzene ring aromaticity and create an available coordination site on the Pd center. These complexes proved to be effective catalysts for the polymerization of NB , 1.4 , and alkenyl norbornenes ( 1.5 , Figure 4).…”
Section: Cationic Single‐component Palladium Catalysts For Polymeriza...mentioning
confidence: 99%
See 2 more Smart Citations
“…This feature allows involvement in polymerization monomers, bearing two, three, or four substituents, which is often impossible for a polymerization of most olefins. Second, there are at least two ways for polymerization of cycloalkenes (ring-opening metathesis polymerization and vinyl (addition) polymerization [1][2][3][4][5]), which give polymers with different structure and properties. Third, owing to well-developed organic tools, such as cycloaddition reactions [6,7], a huge number of cycloalkenes can be prepared, and this provides an opportunity to perform systematic structure-property investigations.…”
Section: Introductionmentioning
confidence: 99%